Cetacean congregation areas in the North Pacific of Costa Rica: management recommendations. - Martínez-Fernández, Damián (2014)
The information on cetacean distribution in the North Pacific of Costa Rica lacks a conservation-oriented analysis. The aim of this study is to identify areas of importance for cetaceans, especially outside the of the existing  protected areas. Previously published data on cetacean sightings between 2004 and 2008 were analyzed, and supplemented by survey effort during the dry season of 2012. A Kriging geo-statistical analysis was used to predict the spatial continuity of cetacean sightings within four study areas. The most important congregation areas for dolphins are: Bahía Santa Elena, Parque Nacional Marino Las Baulas and Reserva Natural Cabo Blanco, they have high densities of dolphin feeding groups. Relevant congregation areas for humpback whales are: Bahía Santa Elena, Playa Tambor, Golfo de Papagayo and Reserva Natural Cabo Blanco. We found areas of high cetacean concentration in the North Pacific, both inside and outside protected areas. Some of the non-protected areas should be prioritized for conservation: Bahía Santa Elena, Bahía Culebra and the surrounding areas of Punta Pargos and Reserva Natural Cabo Blanco. Rev. Biol. Trop. 62 (Suppl. 4): 99-108. Epub 2014 Diciembre 01.